Representasi Ideologi Feminisme dalam Masyarakat Sentani (Kritik Sastra Feminis terhadap Cerita Rakyat Asal-Usul Marga Ongge) - Siswanto Siswanto (Balai Bahasa Provinsi Papua, 2019)
Sentani women have a very comlex role in life. Therefore it is nicknamed as the earth (Kani). Role include the role of domestis and reproductive roles, wihle the production of the publis role of traditional roles. In some cases women are not allowed to play a role in Sentani custom order, but the story of The Origin of Marga Ongge Sentani women have a significant role. So this role can dismissed the notion that women can not play a role in the customary order and also an appreciation for the service of women Sentani role in various aspects of life.